Lung cancer screening. Issue 4 (July 2016) - Tanoue, Lynn T.
Abstract : Purpose of review: Lung cancer screening with low-dose chest computed tomography is now recommended for high-risk individuals by the US Preventive Services Task Force. This recommendation was informed by several randomized controlled trials, the largest of which, the National Lung Screening Trial, demonstrated a 20% relative reduction in lung cancer mortality with annual low-dose chest computed tomography compared with chest radiography. Recent findings: The benefit of lung cancer screening must be balanced against potential harms, including a high false-positive rate with consequent further evaluative studies and invasive testing. It is critical that harms be minimized as screening generalizes to the broad community. Informed decision making between providers and patients should include individualized risk assessment, a discussion of both potential benefit and harm, and tobacco treatment. Given the multiple components required for high quality, screening should ideally occur in the context of a multidisciplinary program. Summary: We are in the early days of lung cancer screening, still with much to learn. Ongoing studies are necessary to refine the definition of a positive screen and develop better methods of distinguishing between true positive and false-positive results. Novel approaches, including the development of multicomponent lung cancer biomarkers, will likely inform and improve our future screening practice.